The mathematics definition discourse : teachers' practices in multilingual classrooms. - Mukucha, Judith (My University, 2012)
Mathematics education studies have shown that part of learning mathematics is learning its language. The language of mathematics is said to include specialised terms and ordinary language terms that have contextual meanings in mathematics. Considering the fact that learners in South Africa are performing poorly in mathematics in the international comparative studies, e.g. TIMSS, there was a need to investigate how teachers facilitate second language learners’ access to the meaning of mathematical terms in multilingual classrooms in South Africa. This study investigated a teacher’s practices in the facilitation of learner access to mathematical terminology in a Grade 11 multilingual class in a township school in Vosloorus, South Africa. The study employed a qualitative approach in investigating Discourse practices that the teacher used to define mathematical terms to second language learners in a multilingual classroom. Direct classroom observations and a teacher interview were the main data gathering methods. The main findings were that the teacher used a combination of interactive practices that involved group work, telling, individual student interactions and initiation, response and evaluation methods. Among definition teaching strategies used were the textbook procedural definition and the textbook descriptive definitions. The chalkboard and the textbook were the main artefacts of the Definition Discourse. The study concludes that the Definition Discourse of the multilingual classroom is a process that involves not only the definition of terms but also an integration of teaching methods and interactive practices where definitions of mathematical terms can be taught even through the eliciting of procedural methods of working out mathematical problems.
Keywords: Discourse; Definition discourse; Mathematical terms; Teacher practices; Classroom discourse